Colonial Transformation of Kenya : The Kamba, Kikuyu, and Maasai from 1900-1939 - Tignor, Robert L. (Book collections on Project MUSE., 1976)
This book takes an entirely new approach to the evolution of cities and of societies in premodern periods. Refining the theory advanced in his earlier study of China and Japan, Gilbert Rozman examines the development of Russia over several centuries with emphasis on the period immediately preceding the Industrial Revolution. He makes possible comparison of urbanization in five countries (including England and France as well as Russia) and develops a systematic framework for analyzing cities of varying size. Treatment of Russia includes a history of urban development prior to 1750, an examin.